Reimagining laboratory‐based immunology education in the time of COVID‐19 - Thomas Wilkinson (Immunology, 2021)
The pandemic has brought challenges to teaching lab and research skills. Here Nigel Francis and colleagues explore the diverse approaches taken to replace lab-based immunology teaching, explain how networks of educators have driven this innovation and discuss the importance of retaining best practice into the future.